Correlation between Smartphone Addiction, Sleep Quality and Physical Activity among Young Adults - S Haripriya; Sanjay Eapen Samuel; M Megha (Journal of Clinical and Diagnostic Research, 2019)
Introduction: In this era of smartphone revolution, the users are prone to get addicted to the convenience provided by it. The youth are the most vulnerable group for smartphone addiction. The smartphone revolution since 2000 is bringing noticeable changes in daily lives of people as it is providing more convenience in day to day life but along with that, there are many adverse-effects in interpersonal relationships, psychological well-being and physical health. Aim: To measure smartphone addiction, assess sleep quality and assess physical activity among young adults and to establish the relationship among the three. Materials and Methods: A cross-sectional study was conducted on 113 students recruited from a health science college in Mangaluru. Smartphone addiction was measured using Smartphone Addiction Proneness Scale-short version (SAPS) which classifies the users as high risk, potential or dangerous risk and no risk users, sleep quality was assessed using Pittsburgh Sleep Quality Index (PSQI) and physical activity assessed using International Physical Activity Questionnaire-Short Form (IPAQSF). Karl Pearson’s correlation coefficient test was used to find the correlation between the three. Results: The correlation coefficient of smartphone addiction and sleep quality was 0.473 indicating a moderately significant positive correlation and that of smartphone addiction and physical activity was -0.335 indicating a negative significant moderate correlation. Conclusion: From the present study it can be concluded that in high risk and dangerous or potential risk users of smartphones the quality of sleep and physical activity tends to decrease. Young adults showing insomnia symptoms should be attentively monitored for smartphone addiction.